2017
DOI: 10.1289/ehp522
|View full text |Cite|
|
Sign up to set email alerts
|

A Case–Control Study of Maternal Polybrominated Diphenyl Ether (PBDE) Exposure and Cryptorchidism in Canadian Populations

Abstract: Background:Polybrominated diphenyl ethers (PBDEs) are flame retardants found in North American household products during the past four decades. These chemicals leach out in dust as products age, exposing individuals daily through inhalation and ingestion. Animal studies suggest that PBDEs disrupt sex hormones and adversely affect development of the reproductive system.Objectives:In the present study, we examined whether there is a link between maternal hair PBDE concentrations and the risk of cryptorchidism (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…The PBDEs have been shown to affect the estrogen receptor signaling pathway, and one of the proposed disruption mechanisms is direct binding of hydroxylated PBDEs to estrogen receptors. 28…”
Section: Research Original Investigationmentioning
confidence: 99%
“…The PBDEs have been shown to affect the estrogen receptor signaling pathway, and one of the proposed disruption mechanisms is direct binding of hydroxylated PBDEs to estrogen receptors. 28…”
Section: Research Original Investigationmentioning
confidence: 99%
“…However, while it has been clearly shown that maternal exposure to estrogenic or anti-androgenic EDCs could induce cryptorchidism in rodents, it remains unproven that such environmental factors are operating in human idiopathic UDT, even if epidemiological studies with statistical correlations do exist as shown above (1, 6, 3335). What could be the mechanism involved?…”
Section: Idiopathic Cryptorchidism and Endocrine Disruptorsmentioning
confidence: 99%
“…One of these prospective studies performed in Nice area (France) reported (1) an increased OR for PCBs (OR 2.74 [1.15, 6.53]) and for DDE concentrations (OR 2.16 [0.94, 4.98]) measured in maternal colostrum. More recently, a case-control study examined whether there was a link between maternal hair polybrominated diphenyl ether (PBDE) concentrations and the risk of UDT in male infants (35) and found that every 10-fold increase of the concentration of maternal hair BDE-99 or BDE-100, was associated with more than a doubling in the risk of UDT (35). Fernandez et al (6), in a small cohort, correlated BPA and propyl-paraben concentrations in the placenta and the occurrence of hypospadias or cryptorchidism.…”
Section: Idiopathic Cryptorchidism and Endocrine Disruptorsmentioning
confidence: 99%
“…Known risk factors for cryptorchidism include maternal gestational diabetes and maternal use of alcohol, acetaminophen or nicotine-containing substances. In recent research, cryptorchidism has been found to be associated with prenatal or early childhood exposure of several chemicals including PBDE ( 133 , 134 ), BPA ( 135 ), parabens ( 135 ), and PBCs ( 134 ). Other researchers have found no association of cryptorchidism with PBBs ( 136 ), organochlorine pesticides ( 137 ), perfluorinated compounds ( 138 , 139 ), or PCBs ( 140 ).…”
Section: Edcs: Female and Male Reproductive Healthmentioning
confidence: 99%